Conidia Production of Metarhizium anisopliae in Bags and Packed Column Bioreactors - Mendez-Gonzalez, Fernando; Loera, Octavio; Favela-Torres, Ernesto (Current Biotechnology, 2018)
Background: Metarhizium anisopliae controls insect pest populations and commercial formulations are based on conidia, regularly produced in plastic bags using rice grains as substrate. This process is labour- intensive and difficult to control; optimisation represents a current problem, even using different types of bioreactors. However, comparisons between Metarhizium conidia production in bags and packed columns are scarce. Objective: The aim of this study was to evaluate the age of the inoculum and two different type of bioreactors on the production of conidia from Metarhizium anisopliae. Method: Metarhizium anisopliae strain CP-OAX was used for conidia production (inoculum of 19 or 25 days old) using steamed rice as substrate either in plastic bags or packed bed bioreactors, the latter with different sizes with air supply. Results: Up to 30% higher conidia yields were obtained in the packed bed bioreactor after 7 days, using a 25 days old inoculum. Respirometric analysis on the packed bed bioreactor determined lag values from 49.08 to 55.23 h and maximum CO2 production rate of 0.295 ± 0.015 mg gidm-1 h-1; maximum sporulation occurred at 56.7 h. Conclusion: Both inoculum age and bioreactor geometry affect conidia production and productivity. The packed column bioreactor allowed higher conidia production and productivity. Air supply at the high scale packed column bioreactor allows metabolic heat removal to maintain isothermal conditions. In addition, the packed bed bioreactor presents advantages, such as reproducibility, the possibility of scaling-up and monitoring the process in terms of temperature and CO2 production.
Keywords: Metarhizium anisopliae